Women and Alcohol : Social Perspectives - Staddon, Patsy (Book collections on Project MUSE., 2015)
This work presents a comprehensive look at the social meaning of women's alcohol use, building a rich social and environmental context through which the contributors can challenge current policy and practice in the field. Raising concerns about the political role of alcohol abuse treatment in policing women's behaviour, it aims to develop a new approach to women's drinking and new ways of aiding recovery at national and local levels.